Introduction to igneous and metamorphic petrology - Winter, John D.; Winter, John D. (New Jersey, Prentice Hall, 2001)
Providing enough background to be rigorous, without being exhaustive, it gives readers good preparation in the techniques of modern petrology; a clear and organized review of the classification, textures, and approach to petrologic study; and then applies these concepts to the real occurrences of the rocks themselves. Requires only a working knowledge of algebra, and makes extensive use of spreadsheets. Includes an accompanying diskette of programs and data files. This book offers unique, comprehensive, up-to-date coverage of both igneous and metamorphic petrology in a single volume and provides the quantitative and technical background required to critically evaluate igneous and metamorphic phenomena.
Appendix 636-643p.; Bibliographical references 644-686p.; Index 687-697p.
Keywords: Rocks-Igneous; Rocks-Metamorphic; Geology